Economic impacts of open access in Europe and the United States - Houghton, John (Septentrio Conference Series, 2014)
The release of the UK Joint Information Systems Committee report Economic implications of alternative scholarly publishing models (Houghton and Oppenheim et al. 2009) generated considerable interest, particularly in the methods used to explore the benefits of open access publishing models, as well as their costs. During 2009, there were a number of follow-on studies. These included national studies in The Netherlands and Denmark, and a three-country comparison, which explored the impacts of alternative scholarly publishing models on one of the larger (United Kingdom), a mid-sized (Netherlands), and one of the smaller European countries (Denmark). This year there have been three further projects. The first focuses on Germany, and brings the German National Licensing Program (NLP) into the mix of alternative scholarly communication models. The second focuses on the United Kingdom, and uses the JISC EI-ASPM model to examine the cost impacts of alternative scholarly publishing models for a sample of UK universities. The third involved further application of some of the underlying methods to exploring the cost-benefit implications of the proposed US Federal Public Research Access Act (FRPAA). This presentation will examine what the methods developed, studies conducted and debate engendered tell us about the viability and sustainability of alternative publishing models, and their potential impacts on research, research infrastructure and the communication and application of publicly funded research findings.